Microstructures and properties of PVDF membranes: effect of the solvent. Issue 1 (27th July 2022) - Luo, Xianxin; Yang, Jing; Zhang, Ruifeng; Li, Hongji; Guo, Yingming; Mu, Ruihua; Zhao, Yamei
Abstract: The polyvinylidene fluoride (PVDF) membranes were synthesized using immersion precipitation technique. The effect of four solvents, N, N-dimethyl formamide (DMF), N, N-dimethylacetamide (DMAC), N-methyl-2-pyrrolidone (NMP), and dimethyl sulfoxide (DMSO) on the water flux and beef serum albumin (BSA) rejection efficiency was reported. The structure and morphology of PVDF membranes were studied using Scanning electron microscopy (SEM), Fourier transform infrared (FTIR), and water contact angle measurements. The cross-section of a membrane formed in a DMF as a solvent exhibit a spongy/fingerlike hybrid structure, while DMSO favors the formation of more porous structure. The increase in the solvent mass fraction facilitates liquid phase separation and solution casting, and changes the structure of PVDF membrane from denser, bicontinuous structure to a looser, stacked structure. Moreover, the results revealed that the properties of PVDF membranes sub-layer are controlled by the diffusion rate of the nonsolvent. The membrane with the best performance was prepared using 80% DMF (mass fraction) as a solvent, and it reached water flux of 66 L·m −2 ·h −1, and 91.53% BSA rejection efficiency.